Oxygen desaturation during a 6-minute walk test as a predictor of maximal exercise-induced gas exchange abnormalities in sarcoidosis - Chenivesse, Cecile; Boulanger, Sarah; Langlois, Carole; Wemeau-Stervinou, Lidwine; Perez, Thierry; Wallaert, Benoit (Journal of Thoracic Disease, 2016)
Background: Common tests for evaluating gas exchange impairment have different strengths and weaknesses. Alveolar-to-arterial oxygen pressure difference (AaDO2) at peak exercise is a sensitive indicator but it cannot be measured repeatedly. Diffusing capacity of the lung for carbon monoxide (DLco) is measured at rest and may be too insensitive to predict the effects of exercise on gas exchange impairment. Oxygen desaturation during a 6-minute walk test (∆SpO2-6MWT) can be measured repeatedly, but its value in sarcoidosis is unknown. Here, we evaluated the ability of ∆SpO2-6MWT and DLco to predict gas exchange impairment during exercise in sarcoidosis. Methods: This retrospective study of 130 subjects with sarcoidosis investigated the relationship between DLco, ∆SpO2-6MWT, and peak AaDO2 using correlation tests, inter-test reliability analyses, and predictive values. For the analyses of inter-test reliability and predictive values, DLco, peak AaDO2, and ∆SpO2-6MWT were considered as binary variables (normal/abnormal) according to previously defined thresholds. Results: Correlation coefficients between DLco, ∆SpO2-6MWT, and peak AaDO2 were intermediate (0.53–0.67, P